Development of Optical Sensor Using ZnO Microflowers as Sensing Material for Organophosphate Pesticide Detection - Salsabiila, Natasya; Suratun Nafisah; Tanjung, Bambang Irawan; Razali, Nur Liyana; Morsin, Marlia; Nulhakim, Lukman; Aziz, Muhammad Reza Kahar (International Journal of Integrated Engineering, 2025)
The widespread usage of organophosphates, such as insecticides, herbicides, and fungicides, presents considerable health hazards to humans owing to their ability to inhibit the acetylcholinesterase enzyme (AChE) in non-target organisms. Prolonged exposure to organophosphates has been associated with neurological disorders, developmental complications in children, and an increased risk of certain cancers. Profenofos and diazinon, a widely utilized organophosphate pesticide for crop pest control, have been categorized as moderately toxic by the World Health Organization (WHO). The identification of profenofos and diazinon residues on crops holds importance for ensuring food safety. This study focuses on the innovative profenofos and diazinon detection method utilizing optical sensors, offering a label-free and real-time measurement scheme. The sensor utilizes zinc oxide (ZnO) with a microflowers structure (ZnO MFs) as the sensing material, chosen for its enlarged surface area, which enhances sensitivity to alterations in the surrounding medium. Synthesized via the solution route method, the ZnO MFs exhibit dimensions of 5.47 ± 0.84 µm in length, 1.30 ± 0.26 µm in width, and an aspect ratio of 4.35 ± 1.02. Profenofos and diazinon concentrations ranging from 1 to 10,000 ppm are used as targeted analytes for sensor testing. The findings demonstrate distinct responses of the optical sensor, with a detection limit (LoD) of 1 ppm. The sensing parameter, Absolute Optical Change (AOC), exhibits its highest value at 1 ppm for profenofos and 100 ppm for diazinon, indicating an optimal sensitivity.